Spatial Modulation-assisted Mobile Diffusive-Drift Molecular Communications - Sharma S.; Mitra R.; Bhatia V. (My University, 2025)
Recently diffusive mobile molecular communication (MC) has emerged as a promising solution for healthcare and environmental sensing applications. In this paper, a molecular index modulation (MIM)-based mobile diffusive-drift MC system under mobility is analyzed. A non-coherent detection algorithm is formulated and results are provided for the symbol error rate (SER) and sum-rate over the diffusive-drift MC channels with/without interlink interference (ILI) and inter-symbol-interference (ISI). The results indicate that the proposed mobile MIM achieves higher sum-rate and delivers lower symbol error. Lastly, effect of various MIM system parameters are studied over MC channel-models. © 2021 IEEE.